2005
DOI: 10.1124/dmd.104.002600
|View full text |Cite
|
Sign up to set email alerts
|

In Vivo Induction of Human Cytochrome P450 Enzymes Expressed in Chimeric Mice With Humanized Liver

Abstract: ABSTRACT:The induction and inhibition of human cytochrome P450 (P450) enzymes are clinically responsible for drug interactions. Although the induction of P450s is investigated using human hepatocytes in the drug development process, there are some disadvantages, such as the decline of the enzyme activity during culture. In the present study, we examined the in vivo induction potency in chimeric mice with humanized liver, which was recently established in Japan to clarify whether this chimeric mouse model would… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
45
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
6
4

Relationship

2
8

Authors

Journals

citations
Cited by 54 publications
(45 citation statements)
references
References 31 publications
0
45
0
Order By: Relevance
“…Many recent publications have unambiguously demonstrated the value of humanized mouse livers for the study of drug metabolism and hepatitis research [7][8][9]21,[23][24][25][26][27][28][29] . However, the albumin-uPA transgenic mouse used for these studies has several major practical limitations.…”
Section: Discussionmentioning
confidence: 99%
“…Many recent publications have unambiguously demonstrated the value of humanized mouse livers for the study of drug metabolism and hepatitis research [7][8][9]21,[23][24][25][26][27][28][29] . However, the albumin-uPA transgenic mouse used for these studies has several major practical limitations.…”
Section: Discussionmentioning
confidence: 99%
“…Katoh et al (2004Katoh et al ( , 2005a reported that cytochrome P450 (P450) isoforms and phase II enzymes in chimeric mice in which the human hepatocyte replacement rate was nearly 90% were almost the same as those in human liver, based on quantitation of enzyme proteins. They also showed that the chimeric mice are a useful animal model to estimate the inductive effect on P450 in humans (Katoh et al, 2005b). We have shown that aldehyde oxidase, a cytosolic drugmetabolizing enzyme, in chimeric mice has functional characteristics almost identical to those of human aldehyde oxidase (Kitamura et al, 2008).…”
mentioning
confidence: 82%
“…Assays such as the transactivation and immortalized hepatocyte assays are extremely high throughput, however they lack the complexity of human hepatocytes which represent the multitude of transcription factors/receptors and their interactions and dynamic drug exposure which occurs in patients were developed by injecting human hepatocytes into SCID mice (80% of the hepatocytes in the liver were of human origin) (67). CYP1A1/2 and CYP3A4 mRNA, protein content, and enzyme activity have been shown to be induced in chimeric mice treated with known human inducers and in hepatocytes isolated from humanized chimeric mice (68)(69)(70).…”
Section: Transgenic/chimeric Animalsmentioning
confidence: 99%